Comparative interpretation of CT and standard radiography of the chest - Coche, Emmanuel E. (Medical radiology. Diagnostic imaging., 2010)
Standard radiography of the chest remains one of the most widely used imaging modalities but it can be difficult to interpret. The possibility of producing cross-sectional, reformatted 2D and 3D images with CT makes this technique an ideal tool for reinterpreting standard radiography of the chest. The aim of this book is to provide a comprehensive overview of chest radiography interpretation by means of a side-by-side comparison between chest radiographs and CT images. Introductory chapters address the indications for and difficulties of chest radiography as well as the technical and practical aspects of CT reconstruction and image comparison. Thereafter, the radiographic and CT presentations of both anatomical variants and the diseased chest are illustrated and discussed by renowned experts in thoracic imaging. Individual chapters are devoted to the imaging features of selected common diseases and disorders, including COPD, lung cancer, pulmonary embolism and hypertension, atelectasis and chest trauma. The book is complemented by online extra material which provides many further educational examples.